Does Frontalis Sling Surgery for Congenital Ptosis Change the Corneal Topography and Refractive Characteristics Postoperatively? - Gandhi A (Dove Medical Press, 2020)
Aastha Gandhi,1 Anuj Mehta,1 Mayuresh Naik2 1Department of Ophthalmology, V.M.M.C & Safdarjung Hospital, Ansari Nagar, New Delhi 110029, India; 2Department of Ophthalmology, H.I.M.S.R & H.A.H. Centenary Hospital, Alaknanda, New Delhi 110062, IndiaCorrespondence: Mayuresh NaikDepartment of Ophthalmology, H.I.M.S.R & H.A.H. Centenary Hospital, Room No. 3 of Eye OPD, 1st Floor of OPD Building, Near GK-2, Alaknanda, New Delhi 110062, IndiaTel +91-8287344576Email mayureshpnaik@gmail.comPurpose: To evaluate the effect of frontalis sling surgery for congenital ptosis on corneal curvature and refractive status.Methods: Prospective study of 60 eyes of 48 patients with severe simple congenital ptosis who underwent surgical correction by frontalis sling surgery. Assessment was done pre-operatively and at 1 week, 1 month, 3 months post-operatively by computerized topographer (Shipp Nippon, CT 1000), IOL master (Carl Zeiss, 500), autorefractometer (Unicos URK-800) and AS-OCT (Cirrus HD-OCT). The results were statistically evaluated to analyze any change in visual acuity, refractive status, keratometry, astigmatism and central corneal thickness (CCT).Results: Three months post-operatively, significant reduction of cylindrical power by − 0.358 D was observed by refraction with corresponding improvement of mean BCVA by 0.24± 0.04 logMAR. Corneal topography showed reduction in astigmatism by − 0.47± 0.95 D; however, the average keratometry did not undergo a significant change. The mean values of astigmatism by IOL master and topographer were comparable. There was significant steepening of the previously flatter meridian (horizontal meridian, in 63.3% patients) while the steeper meridian remained relatively unchanged. A greater reduction in astigmatism was noticed in children in the age group of 5– 10 years.Conclusion: Ptosis surgery modifies the corneal curvature, restoring corneal symmetry and reducing astigmatism; thus changing the refractive status of the patient, which needs to be addressed post-operatively to improve the quality of vision. Children with severe ptosis may benefit from being operated at an early age to achieve better astigmatic reduction.Keywords: topography, ptosis surgery, IOL master